Assesmen Kebutuhan dan Perencanaan Kualitas Kelulusan Siswa-siswi MA. As-Syafi’iyah Mojokerto - Tamam, Mohammad Badru (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Schools assume greater responsibility for preparing students for college, career, and life. accountability is more than just a series of narrow testing and reporting for narrow competency levels. Learning interest in learning and the need to learn how education is increasingly committed to creating learning-centered environments where institutions work actively to help students learn, and assessment of student learning is very important to understand and measure the success of these efforts. The quality of student graduation at MA As-Shafi'iyah. 1) In assessing educational needs to achieve quality education, there are three components, namely students, parents and community members, educators and components involved in the educational process. Besides learning planning also needs to be considered because planning will affect the quality of graduates. 2) Assessment and evaluation are a serious and integral part of the teaching process, which affects not only students, but teachers, the community, and the entire educational environment. 3) one being hypothesized is that informal assessment methods are often used rather than provide more controlled arrangements. Depending on how they are used, the format for informal and formal assessments can include teacher observation of students, oral questions, journal entries, portfolio entries, exit cards, skills inventory, homework assignments, project products, student opinions, interest surveys, referenced criteria , or norm-based tests